HGG-44. Unraveling and Targeting the stem-regulatory network driving invasion in Diffuse hemispheric glioma, H3G34-mutant. (3rd June 2022) - Palma, Alessandro; Ferretti, Roberta; Pericoli, Giulia; Pellegrino, Marsha; Petrilli, Lucia Lisa; Molinari, Valeria; Boult, Jessica K R; Bierke, Lynn; Carai, Andrea; Mastronuzzi, Angela; Robinson, Simon P; Carcaboso, Angel Montero; et al.
Abstract: Diffuse hemispheric glioma H3G34-mutant (DHG-G34) is a pediatric-type high-grade glioma affecting children and young adults. Despite surgery and radio/chemotherapy, patients have a dismal prognosis. The intratumoural heterogeneity and the high infiltrative nature of DHG-G34 cells limit the development of effective therapies. Analysing single-cell RNA sequencing data from a publicly available dataset, we identified a large and distinct sub-population of cells displaying high stem and low differentiation marker expression levels. Gene ontology analyses revealed a gene signature related to cell migration/invasion. This observation is supported by our data on in vitro 3D invasion assay and in vivo orthotopic xenograft models, showing that DHG-G34 disseminating cells are characterised by high expression level of the stem-cell marker NESTIN and low expression level of the differentiation marker GFAP. Following these findings, we developed high-throughput cell-based assays with the aim to screen a library of 1300 FDA-approved compounds and identify drugs able to induce DHG-G34 cell differentiation and inhibit their invasive phenotype. The screen, a co-immunofluorescence assay for NESTIN and GFAP, followed by dose response assays on 3D growth and 3D invasion, led to the identification of 3 FDA-approved drugs, the MEK inhibitor Cobimetinib and 2 HMG-CoA reductase inhibitors, Rosuvastatin and Pitavastatin. These 3 drugs potently induced cell differentiation (decreased Nestin and increased GFAP expression) and inhibited invasion with minimal effect on the proliferation of our DHG-G34 cell line. We are currently extending these findings to additional patient-derived DHG cell lines and we are using these drugs and different omics and imaging technologies to characterize the regulatory networks associated to DHG-G34 stemness, (de)-differentiation and invasiveness. Our work may lead to the identification of new therapeutic approaches for targeting the stem/invasive properties of these aggressive diseases.